تأثير تدريب القدرة SP3 على المستوى الرقمي للسباحين الناشئين - العفيفي، نيفين أمين Alafifi, Nevin Amin (جامعة الزقازيق - كلية التربية الرياضية للبنين, 2014)
يمثل مفهوم التدريب الرياضي محاولة الوصول باللاعب إلى أعلى مستويات الأداء الرياضي التخصصي، والذي يختلف من نشاط إلى أخر ويتفق في الإطار العام للتدريب من خلال محاور ثلاثة للإعداد وهى الإعداد البدني والمهاري والنفسي. وقد لاحظت الباحثة من خلال الخبرات السابقة ومقابلة العديد من مدربي وأساتذة تدريب السباحة، ومتابعة العديد من التدريبات والبطولات ومن خلال الاطلاع على المراجع والأبحاث العلمية أن تدريب القدرة يحسن عنصري القوة والسرعة بشكل أساسي مما يجعل له بالغ الأثر على سباقات المسافات القصيرة، ويفيد في أعطاء السرعة القصوى لمرحلتي البدء والدوران ومرحلة إنهاء السباق، مما يجعل أهمية تدريب القدرة ليس فقط للمسافات القصيرة وإنما أيضا للمسافات المتوسطة والطويلة، ويعمل على زيادة قدرة أكبر عدد من الألياف العضلية على العمل في اتجاه الحركة، وزيادة قدرة السباحين على الوصول لأقصى سرعة مبكراً في بداية السباق مما يؤدي إلى التقدم المبكر على المنافسين وكسب الثقة والتمكن من السباق وبالتالي الفوز بالسباق، كما يحسن أيضاً العمل العضلي عن طريق زيادة كفاءة النظام الفوسفاتي، ويحسن الانتقال من نظام إلى نظام أخر بسهولة وبسرعة دون بطء في السباحة، وبناءاً على ذلك فهي من الطرق الهامة جداً في فترة المنافسات حيث يكون الهدف الوصول لأقصى شدة في التمرين والتركيز على زيادة سرعة التردد وقوة الشدة، ومما سبق فقد وجدت الباحثة ضرورة وجود مجموعة كاملة في كل وحدة تدريبية في فترة الأعداد الخاص وفترة المنافسات. يهدف هذا البحث إلى التعرف تأثير تدريب القدرة SP3 على المستوى الرقمي للسباحين الناشئين واستخدمت الباحثة المنهج التجريبي باستخدام القياس القبلي البعدي لمجموعة تجريبية واحدة تم تطبيق هذا البحث على السباحين الناشئين بنادي الصيد المصري فرع 6 أكتوبر للمرحلة السنية من 15 إلى 17 سنة وكانت من أهم النتائج أن تدريبات القدرة SP3 تؤثر ايجابيا في تحسن المستوى الرقمي لدى سباحي الناشئين. The concept of sports training game to reach the highest specific performance levels, which differs from one activity to another and agree on the general framework of training through the three variables of the preparation of a physical, tectnical and psychological. during the previous experiences and interviewing many of the coaches and swimming training professors, and through following training session and swimming tournaments and through access to references and scientific research The researcher noticed that ability training improves mainly strengh and speed making him a great impact on the sprint, and serves to give Speed maximum of two phases of start-up and spin and stage finish the race, making the importance of training the ability not only for short distances, but also medium and long-distance, and works to increase the capacity of the largest number of muscle fibers to work in the direction of motion, and increase the capacity of swimmers to reach the maximum speed early in the beginning of the race, which lead to early progress on the competitors and gain confidence and mastery of the race and thus win the race, and also improves muscle work by increasing the efficiency of the system of phosphate, and improves the transition from one system to another easily and quickly without the slow swimming, and based on that system, it is very important ways in the period of the competition where the objective to reach maximum intensity in the exercise and focus on increasing the frequency and strength of severe speed, which already has found the researcher that there should be a complete set in each module in the setup and the competitions. This research aims to identify the effect of power training SP3 on numercial level for junior swimmer researcher used the experimental method using measurement tribal dimensional experimental group and one was the application of this research to swimmers junior club Egyptian fishing Branch October 6 Sunni from 15 phase to 17 years and was one of the most important Results ability to "Sp3" exercises affect positive improvement in the digital level at the junior swimmers
Keywords: رياضة السباحة -- التدريب الرياضي -- السباحون -- الأداء الرياضي -- الإنجاز الرقمي